PENGARUH JOB SECURITY, BEBAN KERJA, DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BANK BCA KCU PASAR BARU, JAKARTA - Reza Bagus Andrian; Audita Nuvriasari (JURNAL EKOBIS DEWANTARA, 2023)
This study aims to analyze the effect of job security, workload, and compensation on job satisfaction of Bank BCA KCU Pasar Baru employees, Jakarta. The sampling technique used random sampling with a total sample of 73 employees of BCA KCU Pasar Baru, Jakarta. Data collection techniques using survey techniques with data collection instruments in the form of questionnaires. The results of the study show that job security, workload and compensation have a significant effect on employee job satisfaction.